A study of control mechanisms in micro and nano system-enhanced polymer nanocomposites under mechanical and electrical stimuli: an experimental and computational investigation - Mishra, Raghvendra Kumar (Cranfield University, 2023)
Nanocomposite materials, particularly those reinforced with graphene nanoplatelets (GNPs) and Barium Titanate (BaTiO₃), have been the focus of extensive study within diverse industries aiming to enhance mechanical and electrical properties. This thesis investigates the intricate relationship between external mechanical and electrical stimuli and the effectiveness of these reinforcing agents within nanocomposites, presenting significant findings and novel contributions, while addressing an unexplored aspect within the field. The research highlights a two-part exploration. The first part of the thesis details the creation of GNP/BaTiO₃ polymer nanocomposite fibrils via mechanical stimulation, specifically cold drawing, emphasising the compatibility of recycled polypropylene (PP)/polyethylene terephthalate (PET) blends. The resulting fibrils, exhibiting a significant aspect ratio disparity of 400:1, have demonstrated substantially improved electrical, thermomechanical, and electromagnetic properties. This in-situ mechanical stimulation (cold drawing) not only alters the morphology but also enhances electrical conductivity, limits polymer chain mobility, and reinforces the PP matrix, significantly improving its electrical, thermomechanical, and electromagnetic interference shielding. In the subsequent second part of the thesis, the study explored the integration of graphene-based materials and BaTiO₃ within epoxy composites. Computational modelling and statistical analysis have revealed the influence of these fillers on DC conductivity, dielectric properties, and thermal behaviour. In addition, a comprehensive examination of variations in filler thickness and volume percentage that seemed to significantly impact material’s behaviour has been investigated for the first time under electric fields. Specifically, the investigation into BaTiO₃ nanoparticles and Si-BaTiO3 in epoxy under electric fields has revealed the interplay between electrical stimuli, material properties, and mechanical behaviour, highlighting ferroelectric and piezoelectric effects observed in BaTiO₃ ceramics.i This comprehensive study not only contributes novel findings but also significantly fills a research gap within the field of nanocomposites by presenting an in-depth examination of mechanical and electrical responsiveness, a study that has not been previously undertaken in such a detailed and exhaustive manner. The research conducted, sheds light on the potential for advanced materials in diverse industrial applications and underscores the importance of material selection, offering a pioneering step towards potential industrial utilisation. Additionally, this research offers guidance for further computational exploration, particularly in selecting GNP and BaTiO₃ materials to enhance the electrical and thermal properties of the epoxy matrix
Keywords: Epoxy; Polypropylene; Polyethylene terephthalate; Barium titanate; Graphene nanoplatelets; electric field; Viscoelastic behaviour; thermal behaviour; intrinsic strain